Temporospatial Expression of Fgfr1 and 2 During Lung Development, Homeostasis, and Regeneration - Yuan, Tingting; Klinkhammer, Kylie; Lyu, Handeng; Gao, Shan; Yuan, Jie; Hopkins, Seantel; Zhang, Jin-San; De Langhe, Stijn P. (Frontiers in Pharmacology, 2020)
Fgfr1 and Fgfr2 are dynamically expressed during lung development, homeostasis and regeneration. Our current analysis indicates that Fgfr2 is expressed in distal epithelial progenitors AT2 (alveolar type 2), AT1, club and basal cells but not in ciliated or neuroendocrine cells during lung development and homeostasis. However, after injury, Fgfr2 becomes upregulated in neuroendocrine cells. Epithelial Fgfr1 expression is minimal throughout lung development, homeostasis and regeneration. We further found both Fgfr1 and Fgfr2 are strongly expressed in the cartilage progenitors and airway smooth muscle cells during lung development, whereas Fgfr1 but not Fgfr2 was high in lipofibroblasts and vascular smooth muscle cells. In the adult lung, Fgfr1 and Fgfr2 were mostly downregulated in smooth muscle cells but become upregulated after injury. Fgfr1 remains strong in mesenchymal alveolar niche cells or lipofibroblasts with lower levels of expression in their descendant (alveolar) myofibroblasts during alveologenesis or upon bleomycin injury.